Interstitial flows promote an amoeboid over mesenchymal motility of breast cancer cells revealed by a three dimensional microfluidic model - Huang, Yu Ling (Integr Biol (Camb), 2015)
Malignant tumors are often associated with an elevated fluid pressure due to the abnormal growth of vascular vessels, and thus an increased interstitial flow out of the tumor. Recent in vitro work revealed that interstitial flows critically regulated tumor cell migration within a three dimensional biomatrix, and breast cancer cell migration behavior depended sensitively on the cell seeding density, chemokine availability and flow rates. In this paper, we focus on roles of interstitial flows in modulating heterogeneity of cancer cell motility phenotype within a three dimensional biomatrix. Using a newly developed microfluidic model, we show that breast cancer cells (MDA-MB-231) embedded in a 3D type I collagen matrix exhibit both an amoeboid and a mesenchymal motility, and interstitial flows promote the cell population towards the amoeboid motility phenotype. Furthermore, the addition of exogenous adhesion molecules (fibronectin) within the extracellular matrix (type I collagen) partially rescues the mesenchymal phenotype in the presence of the flow. Quantitative analysis of cell tracks and cell shape shows distinct differential migration characteristics of amoeboid and mesenchymal cells. Notably, the fastest moving cells belong to the subpopulation of amoeboid cells. Together, these findings highlight the important roles of biophysical forces in modulating tumor cell migration heterogeneity and plasticity, as well as the suitability of microfluidic models in interrogating tumor cell dynamics at single-cell and subpopulation level.